2017
DOI: 10.1021/acs.molpharmaceut.7b00504
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Hydrogen–Deuterium Exchange Mass Spectrometry: Correlation of Deuterium Uptake and Long-Term Stability of Lyophilized Monoclonal Antibody Formulations

Abstract: Solid state hydrogen-deuterium exchange with mass spectrometric analysis (ssHDX-MS) has been used to assess protein conformation and matrix interactions in lyophilized solids. ssHDX-MS metrics have been previously correlated to the formation of aggregates of lyophilized myoglobin on storage. Here, ssHDX-MS was applied to lyophilized monoclonal antibody (mAb) formulations and correlated to their long-term stability. After exposing lyophilized samples to DO(g), the amount of deuterium incorporated at various tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…However in some instances, it has been observed that protein stability does not necessarily or at least not only depend on T g . Moorthy et al 40 found that the rank order of T g was poorly correlated to the aggregation propensities of the formulations. Pikal et al 41 found that T g was predictive for the stability of lyophilized human growth hormone in disaccharide systems for storage temperatures near the formulations' T g , whereas for storage at temperatures far below T g , stability behavior seemed to be unrelated to T g .…”
Section: Discussionmentioning
confidence: 99%
“…However in some instances, it has been observed that protein stability does not necessarily or at least not only depend on T g . Moorthy et al 40 found that the rank order of T g was poorly correlated to the aggregation propensities of the formulations. Pikal et al 41 found that T g was predictive for the stability of lyophilized human growth hormone in disaccharide systems for storage temperatures near the formulations' T g , whereas for storage at temperatures far below T g , stability behavior seemed to be unrelated to T g .…”
Section: Discussionmentioning
confidence: 99%
“…The examples in Figure clearly show that deuteration of proteins in the solid state can be different, meaning conformation in the solid state is different, and is influenced by many factors. Articles describing ssHDX MS include conformational analysis of lyophilized monoclonal antibodies during a long-term stability study, the effects of excipients on lyophilized antibody conformation, , and a comparison of conformational effects on monoclonal antibodies as a function of drying by lyophilization or spray drying . Other investigations in which ssHDX MS was applied include analyses of the Fab portion of an antibody, studying how excipients influence the conformation of poly- d , l -alanine, comparing conformation in model proteins that were spray dried, or comparing how spray drying versus lyophilization may affect the conformation of model proteins .…”
Section: Methods Development: Pre-lcmentioning
confidence: 99%
“…9 Studies performed with solid-state hydrogen−deuterium exchange mass spectrometry, 10 a technique that provides peptide-level information about dried protein structure, demonstrate the predictive power afforded by high-resolution data. 11,12 However, residue-level information is essential for gaining a thorough understanding of protein−water interactions and how they relate to the mechanisms of dehydrationinduced unfolding and cosolute-mediated dehydration protection.…”
mentioning
confidence: 99%